Determining the feasibility of identifying creep rupture of stainless steel cladding tubes on-line using acoustic emission technique. Issue 3 (8th June 2015) - Mahendra Prabhu, N; Gopal, K.A.; Murugan, S.; Haneef, T.K.; Mukhopadhyay, C. K.; Venugopal, S.; Jayakumar, T.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to determine the feasibility of identifying the creep rupture of reactor cladding tubes using acoustic emission technique (AET). Design/methodology/approach – The creep rupture tests were carried out by pressuring stainless steel capsules upto 6 MPa at room temperature and then heating continuously in a furnace upto rupture. The acoustic emission (AE) signals generated during the creep rupture tests were recorded using a 150 kHz resonant sensor and analysed using AE Win software. Findings – When rupture occurs in the pressurized capsule tube representing the cladding tube, AE sensor attached to a waveguide captures the mechanical disturbance from the capsule and these data can be advantageously used to identify the creep rupture event of the cladding tube. Practical implications – The creep rupture data of fuel clad tube is very important in design and for smooth operation of nuclear reactors without fuel pin failure in reactors. Originality/value – AE is an advanced non-destructive evaluation technique. This technique has been successfully applied for on-line monitoring of creep rupture of the reactor cladding tube which otherwise could be detected by thermocouple readings only.